Phosphorus removal from molybdenite concentrates via leaching - Navarro, Patricio (2000)
In the process of copper -molybdenum separation is sometimes used reactive phosphorus pentasulfide P2S5 as copper depressant , which causes pollution problems in the final match molybdenite concentrates . The further processing that is performed to these concentrates to produce molybdenum trioxide , produces an increase in the concentration of this element in the final product of 0.05% by hampering commercialization. Due to the above, a study was conducted to hydrometallurgical laboratory scale aimed at finding the optimum conditions of the present process to remove phosphorus so that the content in the molybdenite concentrate is less than 0.04% . The study contemplated a sulfuric acid leaching environment, under different experimental conditions , which were able to remove about 51 % of the phosphorus present in the molybdenite concentrate , lowering the phosphorus content less than 0.03 % values.